Use of ultrasound to facilitate difficult lumbar puncture in the pediatric oncology population - Warhadpande, Shantanu (e-Century Publishing Corporation, 2013)
In the pediatric hematology-oncology population, lumbar punctures (LP’s) are commonly performed to administer intrathecal chemotherapy and obtain CSF samples. Difficult LP’s can arise due to obesity, fibrous tissue formation due to repeated LP procedures, or spinal abnormalities. For difficult LP’s that require imaging-guidance, fluoroscopy is generally?? Fluoroscopy, however, subjects the patient and healthcare providers to radiation while also potentially increasing procedure cost and time. We retrospectively studied the utility of ultrasound-guidance to facilitate LP in 4 pediatric hematology-oncology patients. All 4 patients had a history of difficult LP and 3 of 4 had previously required use of fluoroscopy. With the use of ultrasound, the LP was successfully performed in all 4 patients with one attempt (number of attempts not recorded in one patient). Procedure time was less than 20 minutes in all 4 patients. Our preliminary data suggests that ultrasound may be an efficacious alternative to fluoroscopy. By using ultrasound to identify the landmarks in the lumbar region, the appropriate puncture point can be determined allowing access to the intrathecal space with relative ease. This would decrease the need for fluoroscopy-guidance, the incidence of multiple punctures as well as reducing the procedure time and costs.